Perception and Problem of English Pre-service Teachers in Applying Merdeka Belajar Curriculum During Teaching Practice - Achadiyah, Rachmawati; Azmi, Muhammad Ulul (FKIP - Universitas Tanjungpura, 2024)
Curriculum is updated according to the era's demands which aims at actualizing qualified human resources. The great concept of the curriculum will be superfluous without the teachers